2019
DOI: 10.1002/nau.23970
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal axis after abdominal sacrocolpopexy versus vaginal sacrospinous fixation—a randomized trial

Abstract: Aims To compare postoperative vaginal axis (VA) following vaginal sacrospinous fixation (VSF) or abdominal sacrocolpopexy (ASC) using magnetic resonance imaging (MRI) at postoperative period, in a randomized sample. Methods Seventy‐one patients randomized to VSF with an anterior mesh or ASC were recruited with a mean 27‐month follow‐up for pelvic MRI; 40 patients underwent the examination. VA was calculated in relation to the pelvic inclination correction line. All patients were submitted to physical examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Postmortem muscle fixation and rectal dilatation cause forward movement and shortening of the vagina in cadavers, resulting in a large error between pre- and postmortem evaluations. The boundaries of the uterus and vagina are visible in sagittal MR images; therefore, the positions and axes of the uterus and vagina can be measured and quantified using MRI without distortion ( 3 ). MRI is useful to study the pelvic organs and the functional anatomy of the pelvic floor in living women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postmortem muscle fixation and rectal dilatation cause forward movement and shortening of the vagina in cadavers, resulting in a large error between pre- and postmortem evaluations. The boundaries of the uterus and vagina are visible in sagittal MR images; therefore, the positions and axes of the uterus and vagina can be measured and quantified using MRI without distortion ( 3 ). MRI is useful to study the pelvic organs and the functional anatomy of the pelvic floor in living women.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty percent of parturient women experience POP-related symptoms, and 30–50% of adult women are affected by POP, including 11–19% who require surgery ( 1 , 2 ). The reoperation rate is as high as 30% ( 3 ). Although POP is closely related to damage of the uterine and vaginal supporting structures and uterine and vaginal morphological changes, the pathogenesis of POP is unclear ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Apical defects (uterine prolapse, vault prolapse) are usually corrected by abdominal sacrocolpopexy (ASC) or vaginal sacrospinous fixation (VSF). In a previous study (Juliato et al 10 ), our group showed that using an anterior mesh (VSF-AM) in the anterior compartment, the vaginal axis is deviated in both surgeries, however with no difference between them. 10 Nonetheless, we still have little data about the behavior of the MRI lines of reference for patients operated for POP and their association with physical examination findings and subjective cure using standardized questionnaires.…”
Section: Introductionmentioning
confidence: 72%
“…Magnetic resonance imaging (MRI) has been used to assess vaginal anatomy following POP repair. [3][4][5][6][7][8][9] However, little is known about how vaginal morphology and position relate to prolapse recurrence after POP surgery. In our previous work, the Defining Mechanisms of Anterior Vaginal Wall Descent (DEMAND) study, we showed that apical descent and-to a lesser extent-anterior vaginal wall (AVW) elongation were mechanisms of prolapse recurrence following vaginal surgery.…”
Section: Introductionmentioning
confidence: 99%